CONFLICT BUILDING TECHNIQUE IN THE NOVEL AZAB DAN SENGSARA BY MERARI SIREGAR - Ayudia, Alda Marsya (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2024)
Specifically, this research aims to find and describe the building of conflict in the novel Azab dan Sengsara by Merari Siregar. This research attempts to present the plot pattern of the series of conflicts in the novel Azab and Sengsara through an objective approach and analysis of narratological structuralism studies. The data studied are the actants and conflict events that build the story structure in the novel Azab dan Sengsara. The data were processed and analyzed using the narratological theory of actant schema and functional models from A.J. Greimas. From the results of the analysis of the narrative sequence in the Novel Azab and Sengsara, six complex conflicts were obtained, including; (1) Aminudin's departure to Deli, (2) Helping Mariamin, (3) Educating Sutan Baringin, (4) Fighting over inheritance, (5) Requests from a prospective wife, and (6) Divorce. From the analysis of the six conflicts in the novel, the complexity of the conflict can be seen from the role of the actors who occupy the positions of each component. The plot in the novel Azab dan Sengsara has met the standard of complexity which is characterized by providing a transformation stage in the functional model. Then, the plot in the novel Azab dan Sengsara uses a double plot with several conflicts told from opposite directions.